Case report: Surgical strategies of a giant thrombus from the ascending aorta to the arch - Li, Guanhua; Chen, Yingzhen; Wang, Haikuo; Liu, Yanping; Liu, Hangyu; Sun, He; Wang, Zhiping (Frontiers in Cardiovascular Medicine, 2023)
Large mural thrombi in the relatively normal ascending aorta are extremely uncommon conditions that may lead to major adverse cardiovascular events due to new embolism. Because of its changeable variations, the management of these unstable thrombi is challenging and controversial. The size, morphology, location, embolic involvement, and patients’ conditions are all crucial for therapeutic decision-making. Treatment options include anticoagulation, thrombolysis, surgical thrombectomy, endovascular stenting, and so on. Therefore, surgical strategies should be highly individualized. Herein, we present a rare case of a huge thrombus from the ascending aorta to the arch in a 27-year-old young man. Considering the high risks of catastrophic embolic events, surgical removal of the aortic mass, thromboendarterectomy, and reconstruction of the arterial wall were performed with a satisfactory outcome. This report illustrates our experience of surgical strategies and perioperative treatments for this challenging case and contemporary surgical management for mural thrombi in the ascending aorta was also thoroughly discussed.